The Effect of Demonstration Method on Breast Self-Examination in Young Women at SMAN 1 Telaga Biru - Fatmah Zakaria; Rizky Nikmathulhusna Ali; Olis Datau (Journal of Community Health Provision, 2021)
This research was conducted at SMAN 1 Telaga Biru. The aim was to determine the effect of the demonstration method on breast self-examination in adolescent girls. This research method used an experimental design with a pre-experimental one group pre-test-posttest design. The sample in this study were 56 respondents. Data analysis used the Wilcoxon sign rank test. The results showed that Pvalue = 0.000 which means it is smaller than = 0.05. Thus, there is a difference between breast self-examination conducted by young women before and after being given the demonstration method. It is said that there is an effect of the demonstration method on breast self-examination in adolescent girls at SMAN 1 Telaga Biru.